Analisis Pengungkapan Informasi Penerapan Reklamasi Pascatambang dalam Laporan Keberlanjutan Berdasarkan Ketentuan Peraturan Menteri ESDM No. 07 Tahun 2014 - Linardo, Giandrew; Permatasari, Paulina; Hartono, Leni (VISA: Journal of Vision and Ideas, 2024)
Mining is an activity that utilizes and manages natural resources to meet human needs. In the mining sector, if the mining process is not managed well, mining activities can cause environmental damage such as the decline in soil and water conditions on mining land, disruption of biodiversity, and disruption of social, cultural and economic life in the surrounding community. In this case, mining companies need to carry out post-mining reclamation to reduce the impact of environmental damage. Post-mining reclamation activities need to be disclosed by the company in the sustainability report. This research aims to determine the analysis of disclosure of information on the implementation of post-mining reclamation in the 2021 sustainability report and analyze the suitability of the disclosure based on the provisions of Minister of Energy and Mineral Resources Regulation No. 07 of 2014 (articles 12&16). This research was conducted on coal mining companies that were listed on the Indonesia Stock Exchange (BEI) in 2021. The total sample taken was 34 company units selected using a non-probability sampling technique, namely Purposive Sampling. Based on the criteria created, 13 mining companies were selected and then content analysis and scoring techniques would be carried out based on the criteria in the regulations used. The results of the research analysis show that the disclosure of post-mining reclamation information is still less than optimal/maximum. Based on the established criteria, the average suitability of information disclosure is still quite low, in the range of 45-50%. Thus, mining companies must remain consistent in publishing sustainability reports and need to increase the suitability of disclosure of post-mining reclamation activities in accordance with applicable regulations. For further research, more variables, company sectors and regulatory references should be used to analyze the disclosure of a company's sustainability report.